2018
DOI: 10.3846/jbem.2018.6579
|View full text |Cite
|
Sign up to set email alerts
|

How Does Top Management Team Diversity Matter in Abruptly Dynamic Environments?

Abstract: This study seeks to investigate how top management team (TMT) diversity as a double-edged sword influences a firm’s resilient performance in abruptly dynamic environments and how TMT group longevity moderates this relationship. Abruptly dynamic environment is characterized by low-frequency, substantial magnitude, and high-degree irregularity of change. Utilizing 168 listed electronics firms in Taiwan as the sample, this study incorporated the context of the 2008 global financial crisis as a naturally quasi-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Resilient leadership in the face of the pandemic takes on a broader context: adapting and responding to the current situation, recovering and strengthening, and ensuring continued, sustained, and coherent action. Small and medium enterprises are so sensitive in environment, that managers should keep strength to continue business in all circumstances (Bilan, Mishchuk, Roshchyk, Joshi, 2020;Chen, Liu, 2018). The scientific problem can be formulated by a problematic question: are the organisations under review resilient to emergencies such as the COVID 19 pandemic?…”
Section: Introductionmentioning
confidence: 99%
“…Resilient leadership in the face of the pandemic takes on a broader context: adapting and responding to the current situation, recovering and strengthening, and ensuring continued, sustained, and coherent action. Small and medium enterprises are so sensitive in environment, that managers should keep strength to continue business in all circumstances (Bilan, Mishchuk, Roshchyk, Joshi, 2020;Chen, Liu, 2018). The scientific problem can be formulated by a problematic question: are the organisations under review resilient to emergencies such as the COVID 19 pandemic?…”
Section: Introductionmentioning
confidence: 99%
“…Given that the world is becoming ever more globalized, factors that cause heterogeneity in the labor market as well as in companies themselves are on the rise, e.g., demographic changes, a decreasing number of workers and, thereby, increasing workforce demand, increased employment of women, etc. [6,[10][11][12][13]. In association with globalization, phenomena such as the employment of women in foreign workforces and increased international migration are often mentioned [14].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the situation differs significantly between the primary (agriculture, fishing, forestry), secondary (manufacturing, construction industries), and tertiary (the market and the non-market services sector) sectors in the areas of employment of workers of various age groups, genders, nationalities, etc., as confirmed by national statistics [17]. In the context of the contemporary pan-European activity, concerning the most extensive migration waves from the Middle East and Asia since World War II, diversity management (DM) has taken on a new significance [4,10,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research also showed that the effects of diversity-related attributes on imitation are conditional upon the extent of environmental uncertainty. This finding adds uniquely to the upper echelon literature by bringing in the concept of visibility of attributes in the conversation surrounding the effect of the environmental context in which TMT members make decisions (Chen & Liu, 2018;Qian et al, 2013;Richard et al, 2019). The findings of the research show that team members pay attention to deep-level attributes when faced with adversity (or uncertain situations)…”
Section: Conclusion and Contributionsmentioning
confidence: 68%